Coordinated development of ecosystem services and human well-being is increasing in the Yellow River Basin, though some regions lag behind - Yang, Menghao; Wang, Ming; Zhang, Haipeng; Cao, Lianhai (Frontiers in Ecology and Evolution, 2025)
Exploring and predicting the interaction between ecosystem services (ESs) and human well-being (HWB) is essential for understanding Human-Natural system coupling and sustainable development. Existing studies often use a cascading framework to delineate the transmission of ESs system to HWB system, but rarely reveal the interaction between the two systems. In this study, we treated ESs and HWB as two large systems and investigated the interactive coercing relationship in the Yellow River Basin (YRB) from both the system and subsystem levels. Initially, we estimated ecosystem services value (ESV) for each province in the YRB using the revised equivalent factor method, and evaluated the level of HWB by GRA-TOPSIS model. Subsequently, we analyzed the interactive coercing relationship between ESV and HWB utilizing the coupling coordination degree (CCD) model. Finally, we predicted the development trajectory of the coupled system in the next 20 years. From 2000 to 2020, ESV increased in Qinghai, Sichuan, Gansu, Ningxia, Shaanxi and Shandong, but decreased in Shanxi, Henan, and Inner Mongolia. HWB overall showed a positive upward trend. At the subsystem level, regulation service was the dominant function, and the health and safety well-being was lower than other well-being, but the mental fulfillment well-being improving most slowly. System-level CCD between ESV and HWB has been rising and will continue to do so. The relationship between support service and HWB in Shandong deteriorated, and the relationship between the ESV and HWB in Gansu exhibited a serious lag in ESV and will remain in an uncoordinated state for the next 20 years. Our approaches and results have guiding significance for promoting the coordinated development of HWB and ESs and substantiating the SDGs.